Rethinking Newspaper Survival in the Era of Artificial Intelligence - Obi, Adaku Promise; Nwokeocha, Ifeanyi Martins (International Journal of Religion Education and Law, 2025)
Artificial intelligence and the rise of other technologies have redefined the future of journalism. In all societies today, newspapers are merely struggling to survive, but the potential consequence of technology on the print media differs with the society’s technological history and awareness. AI have made information readily available to the public who were once the audience of newspapers. This paper looks at the potential challenges offered by AI to the traditional newspaper organisations, while also examining the prospect for the future, and calling for new strategies for print media to adapt and thrive in the era of AI. Using Critical Literature Review Approach (CLRA), the paper reviews from existing literature, and the opinions of other scholars about the consequences of AI on the survival of newspaper with focus on Nigeria. The paper concludes that newspapers in Nigeria have continued to survive because of the low level of AI adoption and use in Nigeria and Africa at large, which has made the public to continue to seek information from existing media platforms, but the rise of knowledge will offer severe consequences in the future.